Implementasi Pendidikan Agama Islam dalam Penanaman Akhlak Siswa Sekolah Darul Muhmin Thailand - Sultan Al Fasya; Rizka Harfiani (Journal on Education, 2023)
This study aims to determine the Implementation of Islamic Religious Education in cultivating student morals which is applied by Darul Muhmin Thailand School to students. This research includes qualitative descriptive research. This data collection was carried out by observation, interview and documentation techniques. Meanwhile, in the analysis, the writer uses a qualitative descriptive analysis, namely in the form of written or oral data from the people and observed behavior so that the writer tries to conduct research that is comprehensive in nature about the actual situation. The results of the study found several implementations of Islamic Religious Education activities carried out at the research location, namely the Al-Qur'an tahfizh coaching program, ablution exercises, prayer, remembrance, prayer, adab guidance in study councils, guidance on eating and drinking etiquette, etiquette guidance going home from school, etiquette guidance in the environment carried out by the teacher in instilling religious values ​​in students in the form of all efforts related to the cultivation of morals. Activities are carried out inside and outside the classroom with various strategies and methods that are considered effective for moral development in students.